On a Relation Between the Depth and Complexity of Monotone Boolean Formulas - Sergeev, I. S. (Journal of applied and industrial mathematics, 2019)
We present a sequence of monotone Boolean functions whose depth over the basis {∧, ∨} is c > 1.06 times greater than the logarithm of the formula complexity.